Determination of Bacteroides melaninogenicus Serogroups by Fluorescent Antibody Staining - Lambe, Dwight W. (1974)
Fluorescein isothiocyanate-labeled antibody reagents (conjugates) were prepared to one strain of each of the three subspecies of Bacteroides melaninogenicus: B. melaninogenicus subsp. melaninogenicus, B. melaninogenicus subsp. asaccharolyticus, and B. melaninogenicus subsp. intermedius. These three conjugates were specific; thus, they provided a new serological classification of B. melaninogenicus. The three serogroups were designated A, B, and C. Most test strains (98%) isolated from human clinical specimens were assigned to a specific serogroup by immunofluorescence, and the serogroup of these test strains corroborated the biochemical characterization of the three subspecies of B. melaninogenicus. The conjugates failed to cross-react with other anaerobes or aerobes tested. This fluorescent antibody technique provided a more rapid classification of the three subspecies of B. melaninogenicus than did conventional biochemical methods.